Prevención de incompatibilidades transfusionales al identificar fenotipos rh en pacientes portadores de anticuerpos irregulares, atendidos en el servicio de medicina transfusional de riobamba durante el periodo junio a noviembre de 2015. - Villalba, Carlos (2015)
This work is based on identifying phenotypes of the Rh system using the technique of direct blood typing and evaluation of irregular antibodies of clinical interest, associated with the complications of transfusions, this result correlates compatibility tests for ensure the process and transfused blood product type, preventing the effects of reaction between the antigens present in the units transfused with the antibodies identified in the patient or receiver. The tests used in this work were typing ABO, Rh, evidence of direct and indirect Coombs and compatibility testing, development of the theoretical framework has the characteristics of the associated blood products transfusions and reactions, the antigenic structure ABO and Rh groups in support of the methodological framework is used to scientific, deductive and inductive method, working with a descriptive, explanatory and field research, data collection makes the service of Transfusion Medicine Hospital General Teaching Riobamba, their study allows the affirmation of the hypothesis, in which it is found that by identifying phenotypes blood transfused is prevented from transfusion reactions when identified in a timely manner and correct the irregular antibody in the receptor the result of this work guarantees 100% blood transfusions lack of specific antigen when the blood bag transfused to the irregular antibody having the receiver. All indirect Coombs positive test is recommended tests multipanel thus orients the positive named because the system belongs antibody identified as irregular. correlating Coombs positive results with the phenotypes it is also recommended to ensure the quality of compatibility testing and the cause of the positive test will be known to prevent the transfusion and the reaction.